Literasi Numerasi Siswa Disabilitas SD Negeri 5 Arcawinangun - Muhammad Romli Afri Muhalim; Lia Mareza (Journal on Education, 2024)
This research aims to determine the numeracy literacy of slow learner students at SD Negeri 5 Arcawinangun, as well as the inhibiting and supporting factors that affect the numeracy literacy of slow learner students. This type of research is a case study qualitative research, the research subjects are 3 slow learner students in grade 4 SD Negeri 5 Arcawinangun. Data collection techniques using observation, interviews, and documentation techniques. The results of this study indicate that slow learner students have diverse numeracy literacy skills. The numeracy literacy skills of students with disabilities are influenced by 2 factors, namely internal and external such as the motivation of students with disabilities, family parenting, the teacher's ability to familiarize numeracy literacy questions, and facilities and infrastructure.